The Effect of Acceptance and Commitment Therapy on Illness Perception and Health Promotion Behaviors of Men and Women with Heart Disease - Teimoori, Nasim; Teymoori, Saeid; Bayazi, Mohammad Hossein (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to investigate the effect of acceptance and commitment group therapy (ACT) on disease perception and health promotion behaviors of heart patients. Methods: The present research method was quasi-experimental and the research design was pre-test, post-test and follow-up with a control group. The statistical population included coronary heart patients referred to health centers in Taybad in 2020. Among coronary heart disease, a sample of 30 patients was selected by available sampling method and randomly replaced in an experimental group (acceptance and commitment therapy) and a control group. (15 people in each group). Data were obtained using the Health Promotion Behaviors Questionnaire (Walker et al., 1987) and the Disease Perception Questionnaire (Broadbent et al., 2009). Data were analyzed using repeated measures analysis of variance and Spss.22 software. Results: The effect of group therapy based on acceptance and commitment on disease perception (F=76.48, P<0.001) and health promotion behaviors (F=10.89, P<0.001) had an effect. The result was lasting until the end of the follow-up period. Conclusion: Considering the effectiveness of group therapy based on acceptance and commitment on the improvement of heart patients, this treatment can be used as a method of elective psychotherapy and complementary to medical treatment to reduce psychological symptoms and improve the living standards of heart patients while receiving drug therapy.